(untitled) (Journal of the College of Basic Education, 2022)
Bayt al-Mal is the name given to the institution that managed the financial affairs of the Khilafah State. In the early days of Islam and beyond, this institution took over the process of organizing imports and controlling expenditures. In addition to doing other jobs. Of course, this institution, which developed greatly, was run by workers, employees, and workers appointed by the guardian. matter, but he was the supervisor of this institution and the watcher of everything that entered and left it, and he He is responsible for it as he is responsible for the rest of the state’s facilities in all its aspects.